Behind the Scenes at ApertureScience.com: Portal and Its Paratexts. Issue 4 (June 2023) - Galey, Alan
Portal (2007) presents an unusually complex example for the study of video game paratexts. This article uses the case of the game's promotional website ApertureScience.com to consider how paratextuality and the associated concepts of ephemerality and materiality may be further refined to open up new dimensions of video games as objects of interpretation and play. The article draws from the field of textual studies, which specializes in the particularities of media, and in the entanglement of technical detail with interpretation and meaning. The first part re-evaluates the nature of the book as an analogy for the materiality of video games, and critiques Gérard Genette's conception of bookish paratexts and its applicability to video games. The article then offers a detailed analysis of ApertureScience.com as a paratext, including its satirical critiques of positivism and corporate research, and concludes with a discussion of the materiality of digital paratexts.